Impact of intentional weight loss on diabetic kidney disease. Issue 10 (3rd July 2019) - Holland, John A.; Martin, William P.; Docherty, Neil G.; le Roux, Carel W.
Abstract: Type 2 diabetes mellitus (T2DM) and obesity constitute interwoven pandemics challenging healthcare systems in developed countries, where diabetic kidney disease (DKD) is the most common cause of end‐stage renal disease. Obesity accelerates renal functional decline in people with T2DM. Intentional weight loss (IWL) strategies in this population hold promise as a means of arresting DKD progression. In the present paper, we summarize the impact of IWL strategies (stratified by lifestyle intervention, medications, and metabolic surgery) on renal outcomes in obese people with DKD. We reviewed the Medline, EMBASE and Cochrane databases for relevant randomized control trials and observational studies published between August 1, 2018 and April 15, 2019. We found that IWL improves renal outcomes in the setting of DKD and obesity. Rate of progression of DKD slows with IWL, but varying outcome measures among studies makes direct comparison difficult. Furthermore, established means of estimating renal function are imperfect owing to loss of lean muscle mass with IWL strategies. The choice of optimal IWL strategy needs to be individualized; future work should establish the comparative efficacy of IWL strategies in obese people with DKD to better inform such decisions.